Pemberdayaan Petani Muhammadiyah untuk Mewujudkan Ketahanan Pangan Banyumas - Sugiyatno, Sugiyatno (Proceedings Series on Physical & Formal Sciences, 2023)
Pemberdayaan Petani Muhammadiyah untuk Mewujudkan Ketahanan Pangan Banyumas